Успадкування та ефекти доповненої хромосоми St геному Elymus sibiricus з чужинними ознаками від амфіплоїда Elytricum fertile - Моцний, І.І.; Петрова, І.С.; Чеботар, С.В. (Фактори експериментальної еволюції організмів, 2016)
Aim. Plant pathological and cytological analyses were carried out to detect an alien chromosome in original addition
stocks and to investigate its inheritance and effects. Methods. Plant pathological, cytological and phenotypical analyses
have been applied. Results. The Elymus sibiricus St
genome chromosome addition have been detected. The chromosome
is transmitted through the eggs with a frequency of 19.0% and via pollen of 4.2%. The addition has resulted the asynapsis
and pairing decrease of homologous wheat chromosomes, causing aneuploidy, however, with a very low frequency (6.4%),
low fertility and productivity. Conclusions. The stocks have monosomic or disomic chromosome addition. The addition
was contributed by the collection amphiploid Elytricum fertile and originated from St
genome of Elymus sibiricus. The
alien chromosome carries major linked genes determining hairiness of the leaf upper surface (Hle
) and leaf rust resistance
(Lre
). The addition lines can not be used directly in agricultural practice because of meiotic instability that can lead to loss
of the addition chromosome, low productivity and a number of other undesirable factors associated with the presence of
the alien chromosome.
Keywords: Triticum aestivum, Elymus sibiricus, chromosome addition, inheritance.